Waste Citrus reticulata Assisted Preparation of Cobalt Oxide Nanoparticles for Supercapacitors - Srivastava, Rishabh; Bhardwaj, Shiva; Kumar, Anuj; Singhal, Rahul; Scanley, Jules; Broadbridge, Christine C.; Gupta, Ram K. (Nanomaterials, 2022)
The green, sustainable, and inexpensive creation of novel materials, primarily nanoparticles, with effective energy-storing properties, is key to addressing both the rising demand for energy storage and the mounting environmental concerns throughout the world. Here, an orange peel extract is used to make cobalt oxide nanoparticles from cobalt nitrate hexahydrate. The orange peel extract has Citrus reticulata, which is a key biological component that acts as a ligand and a reducing agent during the formation of nanoparticles. Additionally, the same nanoparticles were also obtained from various precursors for phase and electrochemical behavior comparisons. The prepared Co-nanoparticles were also sulfurized and phosphorized to enhance the electrochemical properties. The synthesized samples were characterized using scanning electron microscopic and X-ray diffraction techniques. The cobalt oxide nanoparticle showed a specific capacitance of 90 F/g at 1 A/g, whereas the cobalt sulfide and phosphide samples delivered an improved specific capacitance of 98 F/g and 185 F/g at 1 A/g. The phosphide-based nanoparticles offer more than 85% capacitance retention after 5000 cycles. This study offers a green strategy to prepare nanostructured materials for energy applications.
Keywords: Citrus reticulata; Co3O4 nanoparticles; characterization; charge storage; dept.phy; peer-reviewed; supercapacitors

Effect of reduce graphene oxide (Rgo) on electrochemical performance of Cus for supercapacitor applications - Singhal, Rahul; Thorne, David; Chaudhary, Manika; Bhardwaj, Shiva; Abazi, Rilind; Gupta, Ram K.; Scanley, Jules; Broadbridge, Christine C.; Singh, B. P.; LeMaire, Peter K.; Sharma, Rakesh K. (2023)
CuS and CuS-rGO nanocomposites were synthesized by the hydrothermal method. The synthesized CuS and rGO-CuS nanocomposite materials were physically characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM) and were evaluated electrochemically for supercapacitor applications. The specific capacitance of CuS was determined to be 207 F/g, 150 F/g, and 97 F/g at a current density of 0.5 A/g, 5 A/g, and 20 A/g, respectively. The rGO-CuS nanocomposite showed improved specific capacitance of 350 F/g, 251 F/g, and 149 F/g at a current density of 0.5 A/g, 5 A/g, and 20 A/g, respectively.
Keywords: CuS; SEM; Supercapacitors; dept.phy; rGO; specific capacitance